2021
DOI: 10.1038/s41380-021-01246-3
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine decreases neuronally released glutamate via retrograde stimulation of presynaptic adenosine A1 receptors

Abstract: Ketamine produces a rapid antidepressant response in patients with major depressive disorder (MDD), but the underlying mechanisms appear multifaceted. One hypothesis, proposes that by antagonizing NMDA receptors on GABAergic interneurons, ketamine disinhibits afferens to glutamatergic principal neurons and increases extracellular glutamate levels. However, ketamine seems also to reduce rapid glutamate release at some synapses. Therefore, clinical studies in MDD patients have stressed the need to identify mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 78 publications
4
33
0
Order By: Relevance
“…For example, the increase in glutamate-glutamine cycling, which may reflect changes in presynaptic release machinery, is time-limited, and may even be decreased at the 24-hour timepoint 64 , such that the major sustained change could be occurring post-synaptically. The effects of ketamine on glutamate release and presynaptic release machinery appears to be much more nuanced than previously thought, with recent evidence showing that ketamine reduces glutamate release and synaptic vesicle recycling in rodents 65 , in line with earlier work suggesting that ketamine administration reduces the number of vesicles 62 . If ketamine reduces synaptic vesicle recycling, we might expect to observe lower SV2A density following ketamine administration.…”
Section: Discussionsupporting
confidence: 75%
“…For example, the increase in glutamate-glutamine cycling, which may reflect changes in presynaptic release machinery, is time-limited, and may even be decreased at the 24-hour timepoint 64 , such that the major sustained change could be occurring post-synaptically. The effects of ketamine on glutamate release and presynaptic release machinery appears to be much more nuanced than previously thought, with recent evidence showing that ketamine reduces glutamate release and synaptic vesicle recycling in rodents 65 , in line with earlier work suggesting that ketamine administration reduces the number of vesicles 62 . If ketamine reduces synaptic vesicle recycling, we might expect to observe lower SV2A density following ketamine administration.…”
Section: Discussionsupporting
confidence: 75%
“…Differently, Stan et al (2014) , by using in vivo measurement with microelectrode array, found that systemic subanesthetic S-ketamine reduced glutamate release in the subiculum, and local application reduced release in the subiculum and PL-PFC. More recently, by using an in vitro and in vivo combined approach (Fast Analytic Sensing Technology, FAST), ketamine was reported to reduce presynaptic glutamate neurotransmission in the subiculum and PL-PFC, with mechanisms implying retrograde stimulation of presynaptic adenosine A1 receptors ( Lazarevic et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased excitation of the cells heightens the risk of brain cell damage or death. Therefore, ketamine stabilizes the glutamatergic system, whose dysfunction causes mood disorders, including PSD [ 110 ].…”
Section: Current Drug Researchmentioning
confidence: 99%